Detection of Rickettsiae in Engorged Ticks from Small Mammals in Malaysia - Madinah, Adrus; Mariana, Ahamad; Mohd Tajuddin, Abdullah (Borneo Journal of Resource Science and Technology, 2014)
Rickettsiae are intracellular bacteria found in ectoparasites such as ticks, lice, fleas, mites and chiggers that can cause emerging infectious diseases throughout the world. There is lacking of information on their distribution and the tick vectors involved. The aim of this study is therefore to determine whether engorged ticks extracted from small mammals (Insectivora, Rodentia and Scandentia) from 15 locations of study areas have any potential health risks to the public. Forty-eight engorged ticks were tested for the presence of rickettsiae DNA using Polymerase Chain Reaction (PCR) targeting a fragment of the rickettsial gene citrate synthase gene (gltA). There was no DNA of rickettsiae detected from the ticks. Further investigations are needed in order to generate more comprehensive information on the potential distribution of rickettsial disease in different locations and habitats that can establish an epidemiological data of rickettsiae in Malaysia.